Memfasilitasi Pengucapan Siswa Pada Suara Konsonan Plosif Melalui Perangkat Lunak Sephonics - Lizamuddin, Ahmad; Zuhri, Mohammad Noor (LITERATUS, 2025)
This research was about facilitating students’ pronunciations on plosive consonant sounds through Sephonics software. It was done at 3rd semester students of ELT Department of Walisongo State Institute for Islamic Studies in the academic year of 2011/2012. The background of this research was the difficulty in learning pronunciation. This research was aimed to responding the following questions; (1) How was the implementation of using sephonics software for teaching pronunciation (plosive consonant sounds) at third semester students of ELT Department, State Islamic Institute of Walisongo, Semarang? (2) Was there any improvement of students’ pronunciation of plosive consonant sounds after being taught using sephonics software? The participant of this research was the 3rd semester students of ELT Department of Education Faculty, Walisongo State Institute for Islamic Studies, Semarang that consisted of 28 students. It was a classroom action research that had two cycles. They were pre-cycle, cycle 1, and cycle 2. The use of sephonics software was used in cycle 1 and cycle 2. The methods of data collection were test and observation in all cycles. The test form was reading aloud that asked students to pronounce some words that contained plosive consonant sounds. Then, the result of test scores was analyzed by using mean to determine whether there was an improvement in each cycle. This study showed that: (1) the first thing that the teacher needed to do to use this software as a teaching aid was that he or she must conduct the class in a language laboratory. If it was not possible, the teacher could conduct the class in a regular classroom by providing several computers or laptops. Then, the students must be grouped based on the number of the computers. The second thing was that this was CALL learning based; the teacher might explain how to use the software in order that the students could practice by themselves outside of class schedule. (2) After collecting data, the result was found that the average (mean) of pre cycle test was 69. Then, it had very significant improvement in cycle 1 and cycle 2. It became 98.7 from cycle 1 test and 99.6 from cycle 2 test. It meant that the research was successful to improve the students’ pronunciation abilities. In conclusion, Sephonics software was successful to facilitate students’ pronunciations on plosive consonant sounds.